Book Review: Society 5.0: A People-centric Super-smart Society - Muhadjir Darwin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
Book Identity: Society 5.0: A People-centric Super-smart SocietyAuthor: Hitachi-U Tokyo LaboratoryPublisher: Springer OpenEdition: First, 2020Number of Page: 177